2020
DOI: 10.3390/ijms21113860
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Characterization of Cyclic NU172 Analogues: A Biophysical and Biological Insight

Abstract: NU172—a 26-mer oligonucleotide able to bind exosite I of human thrombin and inhibit its activity—was the first aptamer to reach Phase II clinical studies as an anticoagulant in heart disease treatments. With the aim of favoring its functional duplex-quadruplex conformation and thus improving its enzymatic stability, as well as its thrombin inhibitory activity, herein a focused set of cyclic NU172 analogues—obtained by connecting its 5′- and 3′-extremities with flexible linkers—was synthesized. Two different ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 100 publications
(195 reference statements)
0
27
0
Order By: Relevance
“…This approach was then extended to NU172, another anticoagulant aptamer [48,49], with which we varied the length and chemical properties of the linker connecting the extremities of the G4 domain, thereby obtaining a focused set of cyclic NU172 derivatives. However, in all cases, a lower inhibitory activity than that of the unmodified aptamer was obtained [50]. These outcomes suggested that increased rigidity of the G4 structure-both in TBA and NU172-as a consequence of the cyclic structure, could somehow reduce the aptamer's affinity for the protein, and thus its bioactivity.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…This approach was then extended to NU172, another anticoagulant aptamer [48,49], with which we varied the length and chemical properties of the linker connecting the extremities of the G4 domain, thereby obtaining a focused set of cyclic NU172 derivatives. However, in all cases, a lower inhibitory activity than that of the unmodified aptamer was obtained [50]. These outcomes suggested that increased rigidity of the G4 structure-both in TBA and NU172-as a consequence of the cyclic structure, could somehow reduce the aptamer's affinity for the protein, and thus its bioactivity.…”
Section: Introductionmentioning
confidence: 93%
“…The end-functionalized TBAs were tested for their anticoagulant activity with respect to unmodified TBA by means of light scattering (LS) experiments, by following the thrombin-catalyzed conversion of fibrinogen into fibrin in PBS, used to mimic physiological conditions [46,47,49,50,93]. Normalized LS intensity curves, as a function of time, allow following the fibrinogen-fibrin conversion because the intensity of the scattered light depends on the size of the objects in the solution.…”
Section: Coagulation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to simultaneously increase the resistance to nuclease degradation and the thrombin binding properties, Di Giusto and colleagues proposed circular multivalent constructs [ 117 , 118 ]. Indeed, circularization is a well-established strategy to improve the performance of aptamers [ 119 , 120 ] and has been efficiently applied to antithrombin aptamers targeting thrombin exosite I [ 96 , 121 , 122 , 123 ].…”
Section: Anticoagulant Aptamersmentioning
confidence: 99%